A igreja como casa da hospitalidade cristã : a experiência do acolhimento desde uma abordagem teológica - Lasch, Rudinei (2017)
In this work we will study the Church as the home of Christian hospitaly. We realized is relevant need in the current context of the hospitality and reception as a virtue exercise. In the ecclesial ambient we found diversity of gifts and charismas that allow the meeting with the different. To sit to the table with the commensals is a space of construction and reconstruction of the human and divine relation. The Church, as the house of christian hospitality, welcomes the pilgrims and has the mission to annouce the Kingdom of God to everyone. Fairly in this subject that is the problem of this dissertative research: how as we turn a Church into a house of hospitality? What is the meaning of the reception experience in the Church since a Christian theological approach? In the hospitality experience happens the commensality, the reception and the dialogue. The reflection is developed at three levels: 1) The Church as house of Christian hospitality: Biblical fundamentals; 2) the reception experience in the Church since a Christian thelogical approach; 3) and the prospects for a Pastoral action in the Church's life.